Color palette from natural dyeing with Rubia dye (Indian Maddar) - Begum Afreen; Shree Vankar Padma (Tekstilna industrija, 2023)
Among the natural dyes, one of the most appealing coloration on Textiles comes from Rubia dye. From ancient times this dye has been used. Rubia is one of the species of the Rubiaceae family. The common madder, covers the members such as Rubia tinctorum (common madder), Rubia peregrina (wild madder), and Rubia cordifolia (Indian madder). Figure-1 shows the picture of Rubia cordifolia. It is a source of red pigment which was of economic importance in Asia, Europe, Africa and Mediterranean in the past. The Indian madder plant has 3-4 colorant moleculesmanjisthin, purpurin and pseudopurpurin and negligible amount of alizarin. These molecules can form dye-mordant-fabric complexes easily due to appropriately placed functional groups such as - hydroxy and enones. The colorant molecules belong to the class of Anthraquinone dyes. The chelation with the metal ion of the conventional mordants or rare earth (RE) mordants is very facile. Rare earth ions have high positive charge and large ionic radii and this ionic nature of the RE+3 ion forms complexation with oxygen atoms of the dye molecules can take place. It has been observed that there is an increase in K/S value as compared to conventional mordants. This can be attributed to coordination effect of the RE mordant. The colorant molecules are capable of forming intensely colored metal complex with the RE salts. Color palette with Rubia dye are derived from the different metal salts used in the dyeing process. Ecofriendly special auxiliaries add brightness to the dyed fabrics.